Biografi Intelektual Habib Abu Bakar Al-Adni Al-Masyhur - Sulton, Achmad (Afkaruna: International Journal of Islamic Studies (AIJIS), 2024)
In every age there will appear scholars who always guard the religion of Allah from enemies of religion who want to destroy and mislead Muslims from the teachings of their true religion, and among the scholars who continue to guard the religion of Allah with their works is Habib Abu Bakr al-Adni Al-Masyhur. The purpose of this study is to analyze the Intellectual Biography of Habib Abu Bakr al-Adni Al-Masyhur. This study uses qualitative research methodology through literature review from primary sources in the form of the works of Habib Abu Bakr al-Adni Al-Masyhur and his Disciples. and secondary sources relevant to this theme. The results showed that Habib Abu Bakr al-Adni Al-Masyhur was one of the Islamic intellectuals who maintained dynamism and revived religious moderation through his intellectual works.